2016
DOI: 10.1371/journal.pone.0166006
|View full text |Cite
|
Sign up to set email alerts
|

CXCL4 and CXCL4L1 Differentially Affect Monocyte Survival and Dendritic Cell Differentiation and Phagocytosis

Abstract: Upon inflammation, circulating monocytes leave the bloodstream and migrate into the tissues, where they differentiate after exposure to various growth factors, cytokines or infectious agents. The best defined macrophage polarization types are M1 and M2. However, the platelet-derived CXC chemokine CXCL4 induces the polarization of macrophages into a unique phenotype. In this study, we compared the effect of CXCL4 and its variant CXCL4L1 on the differentiation of monocytes into macrophages and into immature mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 48 publications
2
32
0
Order By: Relevance
“…3B), but not with pDCs or B cells. Previous data from others and our group indicate clear immunomodulatory effects of CXCL4 at higher doses [21,22]. In co-culture with monocytes, increasing amount of CXCL4 up to 5 μg/mL did not additionally enhance the IL-17 induction (Supporting Information Fig.…”
Section: Cxcl4 Induces Il-17 Production By Cd4 + T Cells When Co-cultmentioning
confidence: 57%
“…3B), but not with pDCs or B cells. Previous data from others and our group indicate clear immunomodulatory effects of CXCL4 at higher doses [21,22]. In co-culture with monocytes, increasing amount of CXCL4 up to 5 μg/mL did not additionally enhance the IL-17 induction (Supporting Information Fig.…”
Section: Cxcl4 Induces Il-17 Production By Cd4 + T Cells When Co-cultmentioning
confidence: 57%
“…For example, the release of pro-inflammatory cytokines, such as CXCL4, by activated platelets plays an important role in the activation of monocytes during acute vascular injury or chronic disease. 24 Hence, the prognostic values of SAA and CXCL4 in this study may be associated to their roles in tumor burden or inflammation. In the current study, we found that lower CXCL4 levels trended toward a poor outcome, which argues against its prognostic correlation being solely attributed to its role as an inflammation marker.…”
Section: Discussionmentioning
confidence: 83%
“…Similar to SAA, CXCL4 is also considered a positive acute‐phase reactant, indicating its level can increase during pro‐inflammatory conditions. For example, the release of pro‐inflammatory cytokines, such as CXCL4, by activated platelets plays an important role in the activation of monocytes during acute vascular injury or chronic disease …”
Section: Discussionmentioning
confidence: 99%
“…Second, CXCL4L1 increase in NHMCs supernatant elevated the expression levels of two prominent inhibitors of kidney inflammation: Smad7 and IkBa. Human mesangial cells were previously shown to express CXCR3, which is the most investigated receptor of CXCL4L1 (21,33,34). Although CXCR3 signaling remains to be investigated in NHMCs, the activation of Smad7 and IkBa by CXCL4L1 was not markedly high in these cells or depending on phosphorylation of the TAK1 or IKK signaling pathways, which are known to induce Smad7 and IkBa highly and transiently (Supplemental Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the strong association between the CXCL4L1 gene and renal function in T1D, the function of mesangial cells may represent only a part of the protective effect of CXCL4L1 expression on renal function. Recently, CXCL4L1 has been shown to induce monocytes to differentiate into distinct macrophage phenotypes different from M1 and M2 in vitro (34). Thus, CXCL4L1 expression is also likely to affect the response of resident immune cells in the kidney.…”
Section: Discussionmentioning
confidence: 99%